Preliminary design enhancement by incorporating set- based design principles and a navigator - Dobrovolskyte, Nora (Cranfield University, 2015)
The need for improvement of Product Development (PD) processes has been demonstrated by a high demand for the aerospace products to be developed quicker and cheaper. Set-Based Design (SBD) can improve the ability to respond faster to customers’ requirements by developing a set of design solutions for possible future product orders in parallel. In SBD participants practise SBCE (Set-Based Concurrent Engineering) by reasoning, developing and communicating about sets of solutions in parallel. As the design progresses, they gradually narrow their respective sets of solutions based on the knowledge gained. As they narrow, they commit to staying within the sets so that others can rely on their communication (Sobek et al, 1999). This research aims to develop logical guidelines for the selection of the PD tools and methods to enable the effective application of the SBD process model guided by a computerized tool, called ‘SBD Navigator’. An integration of the SBD good practices into the collaborator’s PD processes is believed to reduce the possibility of the negative design iteration and to reduce PD time thus providing financial benefits. Understanding the selection of PD methods and tools within manufacturing companies is a starting point of this research. It reveals main causes of poor incorporation of PD methods and tools in the preliminary design phase that might stop businesses from gaining a full range of benefits out of the SBD process model. As time goes on, PD becomes more difficult to manage due to the necessity of the collaboration among business participants in order to create complex and well integrated products. This research project has employed one of the deliverables from the CONGA (Concept Optimisation of Next Generation Aircraft) project which is the SBD process model customized by the collaborating company – Rolls-Royce plc. The RR-SBD process model is presented in chapter 3. [cont.]